2000
DOI: 10.1002/1526-4998(200012)56:12<1098::aid-ps244>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

A nematicidal metabolite fromVerticillium chlamydosporium

Abstract: A bioassay-directed fractionation of cultures of the fungus, Verticillium chlamydosporium, demonstrated nematicidal activity, due mainly to phomalactone. Compared with aldicarb, the lethal activity against Meloidogyne incognita was less, but its activity in suppressing root invasion was similar. The extract also contained monorden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Different stereoisomers of phomalactone ( F ) were isolated and reported previously from various sources [ 15 , 16 , 17 , 18 ], and some papers did not specify the absolute configuration [ 19 , 20 ], while others assigned the (5 R ,6 R ) absolute configuration to the large positive specific rotation [ 21 ], which was opposite to previous studies [ 15 , 16 , 17 , 18 , 22 ]. In order to determine the absolute configuration of phomalactone independently and unambiguously, we performed TDDFT-ECD, TDDFT-OR, and DFT-VCD studies, which consistently confirmed the (+)- cis -(5 S ,6 S ) absolute configuration (see Supplementary Materials ) [ 23 , 24 ].…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Different stereoisomers of phomalactone ( F ) were isolated and reported previously from various sources [ 15 , 16 , 17 , 18 ], and some papers did not specify the absolute configuration [ 19 , 20 ], while others assigned the (5 R ,6 R ) absolute configuration to the large positive specific rotation [ 21 ], which was opposite to previous studies [ 15 , 16 , 17 , 18 , 22 ]. In order to determine the absolute configuration of phomalactone independently and unambiguously, we performed TDDFT-ECD, TDDFT-OR, and DFT-VCD studies, which consistently confirmed the (+)- cis -(5 S ,6 S ) absolute configuration (see Supplementary Materials ) [ 23 , 24 ].…”
Section: Resultsmentioning
confidence: 88%
“…[ 16 ]. It has a wide range of activities such as antifungal, immunomodulating, insecticide, nematocidal, and phytotoxic activity [ 15 , 19 , 33 , 34 , 35 ]. In addition, it has been found to be active against the apicomplexan parasite P. falciparum, with an IC 50 of 84.32 µM [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two compounds namely Phomalactone and Monorden from P. chlamydosporia have nematicidal activity and various biological activities. M. incognita control was less through Phomalactone in comparison with Aldicarb (Khambay et al, 2000). The new compounds which were present in the culture broth of P. chlamydosporia var.…”
Section: Secondary Metabolites Of P Chlamydosporiamentioning
confidence: 86%
“…The gene cluster for the synthesis of RALs compounds in P. chlamydosporia PC-170 has been identified. A total of 30 RALs compounds have been discovered in P. chlamydosporia ( Khambay et al, 2000 ; Hellwig et al, 2003 ; Shinonaga et al, 2009a , b ; Qin et al, 2019 ). RALs compounds have a range of biological activities, but less nematicidal activity has been reported.…”
Section: Discussionmentioning
confidence: 99%